A rapid, non-radioactive screening test for fragile X mutations at the FRAXA and FRAXE loci. Issue 3 (March 1995) - Wang, Q; Green, E; Bobrow, M; Mathew, C G
Abstract : Screening of referrals for the mutations associated with the fragile X syndrome constitutes a significant workload in many genetics laboratories. Since the great majority of these referrals will be negative, there is a need for a rapid and inexpensive screening test. We have developed an assay which allows simultaneous amplification of the triplet repeat sequences at the FRAXA and FRAXE loci by polymerase chain reaction, and detection of the products on non-denaturing gels stained with ethidium bromide. Alleles of normal size are detected, leaving a small minority of samples to be tested by Southern blotting. A PCR based assay for detection of methylation at the CpG island upstream of the FMR-1 gene has also been devised.